Pathways of assimilation of [13N]N2 and 13NH4+ by cyanobacteria with and without heterocysts. - Meeks, J C (1978)
The principal initial product of metabolism of [13N]N2 and 13NH4+ by five diverse cyanobacteria is glutamine. Methionine sulfoximine inhibits formation of [13N]glutamine except in the case of Gloeothece sp., an organism with a thick sheath through which the inhibitor may not penetrate. Thus, glutamine synthetase appears to catalyze the initial step in the assimilation of N2-derived or exogenous NH4+ by these organisms. [13N]Glutamate is, in all cases, the second major product of assimilation of 13N-labeled N2 and NH4+. In all of the N2-fixing cyanobacteria studied, the fraction of 13N in glutamine declines and that in glutamate increases with increasing times of assimilation of [13N]N2 and 13NH4+, and (Gloeothece again excepted) methionine sulfoximine reduces incorporation of 13N into glutamate as well as into glutamine. Glutamate synthase therefore appears to catalyze the formation of glutamate in a wide range of N2-fixing cyanobacteria. However, the major fraction of [13N]glutamate formed by Anacystis nidulans incubated with 13NH4+ may be formed by glutamic acid dehydrogenase. The formation of [13N]alanine from 13NH4+ appears to be catalyzed principally either by alanine dehydrogenase (as in Cylindrospermum licheniforme) or by a transaminase (as in Anabaena variabilis).